HUBUNGAN PENGETAHUAN DAN POLA ASUH TERHADAP PERKEMBANGAN ANAK PRA SEKOLAH DI DESA PARAK WILAYAH KERJA PUSKESMAS BARUGAIA KECAMATAN BONTOMANAI KABUPATEN KEPULAUAN SELAYAR - Wilda Rezki Pratiwi; St. Hasriani; Risnawati Risnawati (Universitas Islam Madura, 2023)
The role of parents is quite complex in raising children, including their parenting style. Besides that, parental supervision and parental knowledge of parenting styles for children also affect children's growth and development. The purpose of this study was to determine the relationship between knowledge and parenting style on the development of preschool-aged children This research uses quantitative research methods. With the design used in this study is Cross Sectional, where in this study only make observations and measurements of variables at a certain time. Unlimited variable measurements must be precise at one time, without follow-up or repeated measurements. The results of research on knowledge show that the calculated X2 value is 16.24 which is greater than the X2 table of 3.841. This can be interpreted that there is an influence between knowledge on the development of preschool-aged children in Parak Village, Bontomanai District, and research on parenting patterns. The calculated X2 value is 9.965, which is greater than the X2 table of 7.815. This means that there is an influence between parenting styles on the development of preschool children in Parak Village, Bontomanai District. Keywords: Knowledge, Parenting, Development